Komunikasi Non Verbal Guru Agama Islam Pada Siswa Tuli Di Sekolah Luar Biasa PKK Bandar Lampung - Desi Setiawati (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2022)
Non-Verbal communication is communication using sign language or silence, Deaf students lose their hearing abilities so that the communication process becomes hampered, which has an impact on speech disorders or the non-development of speech skills resulting in language poverty. Therein lies the importance of the teacher's nonverbal communication in conveying Islamic messages to students. The purpose of this study was to find out the nonverbal communication of Islamic religion teachers to the deaf in SLB/PKK Lampung Province. This research is a qualitative, descriptive field study on nonverbal communication in conveying messages from Islamic religious teachers to deaf students who have hearing loss. This study uses the data collection techniques of observation, interviews, documentation, and data analysis. The results of this study indicate that the nonverbal communication used by the teacher includes body movements, reading speech, and spelling fingers. delivery of material using image media, so that nonverbal communication is very effectively used in the process of conveying Islamic religious message.